2004
DOI: 10.1002/star.200300266
|View full text |Cite
|
Sign up to set email alerts
|

Highly Substituted Carboxymethyl Starch

Abstract: Carboxymethyl starches (CMS) with a degree of substitution (DS) in the range of 0.5 to 1.5 and reagent yields about 70% were synthesised under heterogeneous reaction conditions. Starting from a standard procedure for manufacturing low substituted CMS the molar ratios of the reagents were increased. Under these conditions starch particles agglomerated during the reaction and the stirrer stopped. The reaction conditions (pulp density, addition of dispersing and water binding agents, pressure, sequence of reagent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 11 publications
3
28
0
Order By: Relevance
“…Further increase in NaOH dosage caused an inactivation of MCA and hence it is consumed in the side reaction. 11 This observation is consistent with previous reports on carboxymethyl corn and amaranth starch. 12…”
Section: Influence Of Various Molar Ratios Of Naoh To Starch (Agu) Onsupporting
confidence: 94%
“…Further increase in NaOH dosage caused an inactivation of MCA and hence it is consumed in the side reaction. 11 This observation is consistent with previous reports on carboxymethyl corn and amaranth starch. 12…”
Section: Influence Of Various Molar Ratios Of Naoh To Starch (Agu) Onsupporting
confidence: 94%
“…Each AGU contains three hydroxyl groups (C 2 , C 3 , and C 6 ); therefore, the DS lies between zero and three. From the studies of Volkert et al (6) and Heinze et al (7), substitution in the order C 2 >C 6 >C 3 was indicated.…”
Section: Introductionmentioning
confidence: 97%
“…Many studies have discussed the influence of reaction medium, reagent concentrations, reaction temperature, and reaction time as main factors that determine the DS of carboxymethyl starch (6,(8)(9). Some of these studies determined the effects of reaction parameters on the carboxymethylation of starch by changing one variable while keeping the others constant.…”
Section: Introductionmentioning
confidence: 99%
“…However, if functional groups are introduced into the polysaccharide structure, they can form chemical bonds with minerals. For instance, Volkert et al (2004) reported that introduction of carboxyl groups into the starch markedly improved its calcium-binding capacity. In addition, the interaction of polysaccharides with minerals has been reported to be strongly dependent on pH (Liu et al 2000).…”
Section: Effect Of Polysaccharide Type and Precipitation Processmentioning
confidence: 99%